Conformal Killing-Yano Tensors on Manifolds with Mixed 3-Structures - Ianus, S.; Visinescu, M.; Vîlcu, G.E. (Symmetry, Integrability and Geometry: Methods and Applications, 2009)
We show the existence of conformal Killing-Yano tensors on a manifold endowed with a mixed 3-Sasakian structure.